Multi-Physics of Dynamic Elastic Metamaterials and Earthquake Systems - Yakovleva, A. A.; Movchan, I. B.; Misseroni, D.; Pugno, N. M.; Movchan, A. B. (Frontiers in Materials, 2021)
Microstructured materials, namely metamaterials, are one of the most relevant topics of the recent period due to their interdisciplinary nature. Driven by their wide range of applications, we provide an overview of a class of elastic solids which embed dynamic microstructures capable of trapping energy when subject to dynamic loads. Based on the recently developed modelling approaches, we show several applications related to wave cloaking, Filtering and also multi-structured surfaces, often referred to as meta-surfaces. These culminate in the analysis of a practical example, based on a real-life recent seismic event induced by a hydrofracture exploration. The latter shows the viability of the vibration analysis in the assessment of the seismic response, and also the role of meta-surfaces as localisers of vibrations.